Distribution of nitrogen compounds in important sections of sugar beets - Bąk, Paulina; Antczak-Chrobot, Anet; Wojtczak, Maciej (Biotechnology and Food Science, 2015)
In literature the beet is often described as consisting of the following technologically important sections: crown, root and tail. The aim of the study was to determine the distribution of nitrogen compounds in the technologically important beet sections of untopped sugar beets with particular emphasis on the content of nitrate and nitrite. The Finezja sugar beet variety had been collected from the clamps in one of the Polish sugar factories in October during 2013/2014 campaign. The untopped sugar beets were divided into three sections: crown, root and tail. The content of total amount of nitrogen, proteinaceous nitrogen, α-amino nitrogen, the sum of the amide and ammonia nitrogen, nitrates and nitrite in these sections were determined. Although the crown of the sugar beet represented only 14.7% of it mass, this section contained on average 30% of the total quantity of α-amino acids as well as amide and ammonia nitrogen. This section contained approximately 77% of the total quantity of nitrate and 88% of nitrite. Untopped sugar beets would introduce much higher amounts of nitrogen compounds in comparison to topped raw material.